The Effect of Giving Ambon Banana (Musa Paradisiaca Var Sapientum Linn) on Blood Pressure among Pregnant Mothers with Hypertension - Fara Berliana; Bunga Tiara Carolin; Putri Azzahroh (KHD Production, 2024)
The incidence of hypertension in pregnant women constitutes 33.07% of pregnancy complications which is one of the factors causing maternal death. Pakuhaji Regional Hospital found that the incidence of hypertension was around 40%. One good diet method is to reduce salt intake and increase potassium intake. Giving Ambon bananas is high in potassium which can lower blood pressure. This study aimed to determine the effect of giving Ambon banana (musa paradisiaca var sapientum linn) on blood pressure in pregnant women with hypertension at Pakuhaji Regional Hospital in 2023. Pre-experimental research with a one group pretest and post test design. The sample in this study consisted of 35 respondents using a purposive sampling technique. Data were analyzed using a paired sample t-test which was previously tested for normality. The results of univariate analysis before giving Ambon bananas averaged systole 159.54 mmHg and diastole 102.89 mmHg, after giving Ambon bananas it decreased with an average systole of 141.57 mmHg and diastole 86.80 mmHg. The results of bivariate analysis with paired sample t-test giving Ambon bananas a value of 0.000. There is an effect of giving Ambon bananas (Musa paradisiaca var sapientum Linn) on blood pressure in pregnant women with hypertension. It is hoped that pregnant women can increase the knowledge of pregnant women with hypertension that apart from using medicines from doctors, they can also use Ambon bananas.